2010
DOI: 10.1111/j.1600-0765.2010.01326.x
|View full text |Cite
|
Sign up to set email alerts
|

Porphyromonas gingivalis promotes murine abdominal aortic aneurysms via matrix metalloproteinase-2 induction

Abstract: These findings demonstrate that challenge with P. gingivalis, but not with A. actinomycetemcomitans, can accelerate, or even initiate, the progression of experimental AAA through the increased expression of MMPs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
52
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(53 citation statements)
references
References 56 publications
1
52
0
Order By: Relevance
“…31) We also revealed that a pharmacological inactivation of MMPs resulted in the prevention of abdominal aortic aneurysm development. 32) Thus, MMPs are key factors connecting periodontitis and cardiovascular remodeling; an intervention might be effective to prevent the progression.…”
Section: Discussionmentioning
confidence: 90%
See 1 more Smart Citation
“…31) We also revealed that a pharmacological inactivation of MMPs resulted in the prevention of abdominal aortic aneurysm development. 32) Thus, MMPs are key factors connecting periodontitis and cardiovascular remodeling; an intervention might be effective to prevent the progression.…”
Section: Discussionmentioning
confidence: 90%
“…This model is known to represent chronic bacteremia with periodontitis as previously described. [31][32][33] Although this model has been widely used as a chronic periodontitis model, it does not directly represent clinical periodontitis. Other murine periodontal bacteria infection models have been reported; an intravenous injection model represents an acute periodontitis and an intragingival injection model represents local infection.…”
Section: Discussionmentioning
confidence: 99%
“…1) Recently, we demonstrated that P. gingivalis deteriorated AAA [8][9][10] and wire-injury induced arteriosclerosis 14) in animal models. Furthermore, we demonstrated that A. actinomycetemcomitans aggravated ventricular remodeling after myocardial ischemia 15) and pressure overload-induced myocardial hypertrophy.…”
Section: Discussionmentioning
confidence: 99%
“…[5][6][7] Recently, we revealed that P. gingivalis worsened AAA development while A. actinomycetemcomitans did not alter its development in experimental murine AAA models. 8) We clarifi ed that P. gingivalis affected AAA progression through toll-like receptors (TLRs) and matrix metalloproteinases (MMPs). [8][9][10] P. intermedia is also known to be an important periodontal pathogen in cardiovascular diseases.…”
mentioning
confidence: 99%
See 1 more Smart Citation